Competitive Antagonism of Anesthetic Action at the γ-Aminobutyric Acid Type A Receptor by a Novel Etomidate Analogue with Low Intrinsic Efficacy - Ma, Celena (Anesthesiology, 2017)
BACKGROUND: The authors characterized the γ-aminobutyric acid type A (GABA(A)) receptor pharmacology of the novel etomidate analogue naphthalene-etomidate, a potential lead compound for the development of anesthetic-selective competitive antagonists. METHODS: The positive modulatory potencies and efficacies of etomidate and naphthalene-etomidate were defined in oocyte-expressed α(1)β(3)γ(2L) GABA(A) receptors using voltage clamp electrophysiology. Using the same technique, the ability of naphthalene-etomidate to reduce currents evoked by GABA alone or GABA potentiated by etomidate, propofol, pentobarbital, and diazepam was quantified. The binding affinity of naphthalene-etomidate to the transmembrane anesthetic binding sites of the GABA(A) receptor was determined from its ability to inhibit receptor photoaffinity labeling by the site-selective photolabels (3)[H]azi-etomidate and R-(3)[H]mTFD-MPAB. RESULTS: In contrast to etomidate, naphthalene-etomidate only weakly potentiated GABA-evoked currents and induced little direct activation even at a near-saturating aqueous concentration. It inhibited labeling of GABA(A) receptors by (3)[H]azi-etomidate and R-(3)[H]mTFD-MPAB with similar half-maximal inhibitory concentrations of 48 μM (95% confidence interval, 28 to 81 μM) and 33 μM (95% confidence interval, 20 to 54 μM). It also reduced the positive modulatory actions of anesthetics (propofol > etomidate ~ pentobarbital), but not those of GABA or diazepam. At 300 μM, naphthalene-etomidate increased the half-maximal potentiating propofol concentration from 6.0 μM (95% confidence interval, 4.4 to 8.0 μM) to 36 μM (95% confidence interval, 17 to 78 μM) without affecting the maximal response obtained at high propofol concentrations. CONCLUSION: Naphthalene-etomidate is a very low efficacy etomidate analog that exhibits the pharmacology of an anesthetic competitive antagonist at the GABA(A) receptor.